The Effectiveness of Student Team Achievement Division (STAD) and Group Investigation (GI) on News Text Writing Skills with Event Image Media in Grade VIII Junior High School Students - Sistiani, Nawang; Suta Wardianto, Bayu (International Proceedings of Nusantara Raya, 2024)
This study purpose to determine the effectiveness of the model student team achievement division (STAD), determine the effectiveness of the model group investigation (GI), and compare the degree of effectiveness of the student team achievement division (STAD) and group investigation (GI) to the skill of writing a news text with the media images of events at class VIII JHS. This research is a quasi-experiment and using matching pretest-posttest comparison group design. The result of this study indicate that the student team achievement division (STAD) effectively applied, model of group investigation (GI) effectively applied, and model of group investigation (GI) is more effective than the applications of the model student team achievement division (STAD) the skill of writing news text with the media images of events at class VIII JHS with the results tcount > ttable or 2,19 > 2,00.